2019
DOI: 10.1016/j.dib.2019.104183
|View full text |Cite
|
Sign up to set email alerts
|

Data on study of hematite nanoparticles obtained from Iron(III) oxide by the Pechini method

Abstract: This article presents the data on α-Fe 2 O 3 nanoparticles synthesized via Pechini method using iron(III) oxide precursor from steel industry. It is important to highlight the added value that is given to an industrial waste. The samples were characterized by thermal analysis (DTA, TG), X-ray diffraction (XRD), and Fourier transform infrared spectroscopy (FTIR). The TG showed three mass changes, whereas DTA resulted in three anomalies. X-ray diffraction pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…This results in a shift to higher frequencies in the FTIR spectra. The stretching vibration frequencies of ferric oxide which usually occurring around 300, 400 and 500 cm −1 are absent, because they fall below the detection limit of the instrument [29,30]. M-O bond frequencies generally occur between 270 and [30,31].…”
Section: Infrared Analysismentioning
confidence: 97%
“…This results in a shift to higher frequencies in the FTIR spectra. The stretching vibration frequencies of ferric oxide which usually occurring around 300, 400 and 500 cm −1 are absent, because they fall below the detection limit of the instrument [29,30]. M-O bond frequencies generally occur between 270 and [30,31].…”
Section: Infrared Analysismentioning
confidence: 97%
“…For adsorption at 25 • C, R 2 average values of 0.9921 and 0.9974 were obtained for AC and MAC, respectively. These results suggest that limiting of the adsorption mechanism was mainly due to chemical interactions (chemisorption) that involve valence and electron exchange forces between the adsorbent and adsorbate [48,49]. In the literature it is reported that the pseudo-second-order model better predicts the adsorption of 2,4-D onto carbon's surface, as well as that of pesticides as adsorbates such as ametryn, aldicarb, dinoseb, diuron [50], and carbofuran [5].…”
Section: Kinetic Studymentioning
confidence: 90%
“…The second weight loss is due to the phytochemicals present in the hematite nanoparticles which evaporated. And the third weight loss is due to the formation of a completely pure alpha-Fe 2 O 3 phase [58][59][60]. The endothermic peaks were observed at the DTA thermograph at 286, 916, and 910°C temperatures.…”
Section: W-h Plot Methods With Udm (Uniform Deformation Modelmentioning
confidence: 97%
“…The endothermic peaks were observed at the DTA thermograph at 286, 916, and 910°C temperatures. The peaks were obtained in the DSC thermograph due to the evaporation of water and organic substances and crystallization of iron oxide [58][59][60].…”
Section: W-h Plot Methods With Udm (Uniform Deformation Modelmentioning
confidence: 99%